Factors Related to Nurses' Motivation in Carrying Out Nursing Documentation in the Surgical and Internal Rooms at Kudungga Sangatta Regional Hospital - Nurhasanah; Rasmun; Amirudin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the factors related to nurses' motivation in carrying out nursing documentation. The type of research is an analytical survey with a cross sectional design. The population is all nurses in the Surgical (Emerald) and Internal (Nilam) Rooms at Kudungga Sangatta Regional Hospital, totaling 38 people. The sampling technique used total sampling. The research time was 26-31 May 2023. The instruments were motivation, knowledge, length of work and rewards with Cronbach alpha > 0.6. Data analysis used the chi-square test. Factors related to nurses' motivation in carrying out nursing documentation include knowledge (p value 0.049 < α : 0.05), length of work (p value 0.023 < α : 0.05) and reward (p value 0.010 < α : 0, 05).